(untitled) (Research, Society and Development, 2024)
The growing demand for whole-grain products is associated with the benefits of the macronutrients and micronutrients found in cereals and pseudocereals. However, contaminant presence, especially mycotoxin-producing fungi on the outer layers of grains, can compromise sanitary quality and pose health risks to consumers. This review aimed to compare the grinding of whole and fractionated grains regarding the microbiological quality of whole cereal and pseudocereal flours. Whole grains present a higher risk of contamination, requiring strict measures from planting to distribution, including proper post-harvest practices, storage, milling, and packaging, with efficient tracking of fungi and mycotoxins. For wheat, the control steps used in refined flour production can be adopted for whole-grain flour, complemented by surface treatments to remove contaminants. For whole corn, type classification criteria need to be stricter than those currently established by legislation. In pseudocereals, classification and control practices are still underdeveloped, requiring specific protocols for each type of grain and its potential contaminants. Additionally, many grains marketed lack clear regulations for contaminant control. Reducing mycotoxin levels in grains will require technological advancements, such as artificial intelligence and Big Data, enabling monitoring and safety improvement throughout the production chain, from planting to the final consumer, contributing to the supply of safer and healthier products.